Physical layer security performance analysis of multi-antenna full-duplex relay aided heterogeneous cellular network - Zhou ZHONG; Bo ZHANG; Xiaohui QI; Kaizhi HUANG (Tongxin xuebao)
To alleviate the spectrum shortage problem and security threats in heterogeneous network (HetNet),multi-antenna full-duplex relay was introduced for communication between femto base station (FBS) and legitimate user.With the aid of multi-antenna full-duplex relay in FBS network,the secrecy performance of HetNets could be improved.Under a stochastic geometry framework,the fundamental analysis model to evaluate the secrecy performance in multi-antenna full-duplex relay aided HetNet was set up.To be specific,the exact expressions for the secrecy outage probability of the typical user,serving relays and HetNet were derived respectively.Then,based on the theoretical analyses and simulation results,the influences of transmit power and antenna number of both macro base station and FBS on secrecy performance in HetNet were examined.Finally,the results show that introducing multi-antenna full-duplex relay for FBS networks improves the secrecy performance of HetNet.